2019
DOI: 10.1029/2018jc014907
|View full text |Cite
|
Sign up to set email alerts
|

Water Mass Characteristics of the Antarctic Margins and the Production and Seasonality of Dense Shelf Water

Abstract: Conductivity-temperature-depth data from instrumented seals of the Marine Mammals Exploring Oceans from Pole to Pole program are analyzed to characterize the water masses and the seasonality of the marginal seas. Bottom temperatures are found to be in a cold regime in Dense Shelf Water (DSW) producing regions, identified in this study as the southern Weddell Sea, Cape Darnley, Prydz Bay, Adélie Coast, and the western Ross Sea. DSW occupies the bottom of the Weddell and Ross Sea continental shelves throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…Unlike the Totten region, both mCDW and DSW are found in Vincennes Bay. Although that could indicate that where and when DSW is present in the bay there is no mCDW (Narayanan et al., 2019), the interplay in the polynyas suggests otherwise. Both DSW and mCDW were found to be accessing the local ice shelf cavities and driving basal melt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the Totten region, both mCDW and DSW are found in Vincennes Bay. Although that could indicate that where and when DSW is present in the bay there is no mCDW (Narayanan et al., 2019), the interplay in the polynyas suggests otherwise. Both DSW and mCDW were found to be accessing the local ice shelf cavities and driving basal melt.…”
Section: Discussionmentioning
confidence: 99%
“…Silvano et al. (2017) showed that meltwater input to the Dalton Polynya results in increased stratification and impedes winter convection near the Totten Glacier, which allowed mCDW intrusions to persist on the shelf (Narayanan et al., 2019). Our observations in Vincennes Bay show that mCDW intrusions are driving local glacial melt, which increases stratification making it harder for polynyas to generate deep convection.…”
Section: Discussionmentioning
confidence: 99%
“…The 2004-17 MEOP data (Roquet et al 2014Treasure et al 2017) offer a means to investigate Antarctic shelf water masses. Narayanan et al (2019) showed that the presence of dense shelf waters coincides with an absence of warmer Circumpolar Deep Water. As part of that study, mean temperatures were quantified at depths ranging from 250 m to the bottom, and from the coast or ice shelf edge (75 km and beyond) to the continental shelf and slope (shallower than 3000 m).…”
Section: ) Variability In the Decline Of Antarctic Bottom Water Volumementioning
confidence: 99%
“…Most (68%) "ice-shelf" supercooled profiles are shallower than 600 m. Only 14% of the "ice-shelf" profiles have potential supercooling above 200 m, and in 10% of the cases, it occurs above the permanent pycnocline (Figure 4h). The rather deep signal of potential supercooling in these profiles is largely associated with DSW in the four locations identified as source regions for AABW: the Weddell Sea, Ross Sea, Adélie Coast, and Prydz Bay (Figure 4e; Foldvik et al, 2004;Narayanan et al, 2019). While the "ice-shelf" criteria capture 10.1029/2020GL090242 supercooled water at depth, ISW that rises toward the surface will likely fall into our category characterized by the presence of potential supercooling over the entire water column or a maximum degree of supercooling at depth and at the surface (section 2.3).…”
Section: Resultsmentioning
confidence: 98%
“…Thus, the resulting Ice Shelf Water (ISW) would be potentially supercooled relative to a corresponding surface freezing point of about 1.85°C. Depending on its density, ISW either sinks as potentially supercooled Dense Shelf Water (DSW) and may leave the continental shelf to form Deep Waters and Antarctic Bottom Water (AABW; Foldvik et al., 2004; Narayanan et al., 2019) or rises along the bottom of the ice shelf (Countryman, 1970; Lewis & Perkin, 1986, Figure 1). If ISW plumes rise, their local freezing point may increase above the water temperature due to the decreasing pressure, leading to in situ supercooling.…”
Section: Introductionmentioning
confidence: 99%